Characterisation and molecular cloning of an erythromycin resistance plasmid of Lactococcus lactis isolated from chicken cecum - A.R., Raha; Ross, E.; Yusoff, K.; Manap, M.Y.; Ideris, A. (2002)
An erythromycin resistance plasmid, pAJ01 was isolated from Loctococcus lactis isolate C5 that was isolated from a healthy two-week-old chicken cecum. A 4 kb plasmid was transformed into plasmidless L. lactis MG1363 before a restriction endonuclease map was constructed. It was then fused with pUC19 to form pAJ02, which can replicate in Escherichia coli XLI-Blue as well as L. lactis MG1363. The plasmid was stably maintained in Lactococcus for more than 100 generations.